2020
DOI: 10.1002/cptc.202000066
|View full text |Cite
|
Sign up to set email alerts
|

Photon Transport and Hydrodynamics in Gas‐Liquid Flow Part 2: Characterization of Bubbly Flow in an Advanced‐Flow Reactor

Abstract: The Corning® G1 Advanced-Flow™ Reactor (G1 AFR) is a commercially available meso-scale reactor which promotes a bubbly flow regime and was previously used to scale-up gasliquid photoreactions. In this paper, we study how the photon transport and hydrodynamics affects the performance of G1 AFR in gas-liquid flow. This was realized by analyzing the flow pattern, liquid residence time, photon flux per liquid volume and optical pathlength using image analysis, residence time distribution (RTD) experiments and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Their reactors consist of typical fluidic modules (e.g., Lab Reactor ∼2.7 mL, G1 Photo Reactor ∼9 mL, and G3 Photo Reactor ∼60 mL), with the patented heart-shaped designs (Figure E). This shape is used in the reactors available of their Advanced-Flow Reactor (AFR) products because it enhances heat- and mass transfer (e.g., for scaling gas–liquid reactions). The modules can be irradiated by the available (monochromatic) LEDs from both sides, and multiple modules can be connected to scale up total reactor volume and throughput. Creaflow also offers scalable flow reactors and the oscillatory flow HANU reactors (5–150 mL) is especially designed for photochemistry (Figure F) .…”
Section: Reactor Design and Scale-upmentioning
confidence: 99%
“…Their reactors consist of typical fluidic modules (e.g., Lab Reactor ∼2.7 mL, G1 Photo Reactor ∼9 mL, and G3 Photo Reactor ∼60 mL), with the patented heart-shaped designs (Figure E). This shape is used in the reactors available of their Advanced-Flow Reactor (AFR) products because it enhances heat- and mass transfer (e.g., for scaling gas–liquid reactions). The modules can be irradiated by the available (monochromatic) LEDs from both sides, and multiple modules can be connected to scale up total reactor volume and throughput. Creaflow also offers scalable flow reactors and the oscillatory flow HANU reactors (5–150 mL) is especially designed for photochemistry (Figure F) .…”
Section: Reactor Design and Scale-upmentioning
confidence: 99%
“…A mass flow controller (Brohnkhorst, F-200CV-005) calibrated for O 2 and a double syringe pump (Harvard Apparatus) were used to control the gas and the liquid feed, respectively. The concentration of the tracer was measured using a stainless steel flow cell connected with optical fibers to a deuterium-halogen light source (AvaLight-DH SBAL, Avantes) and a UV–vis spectrometer (AVASPEC-ULS2048CLEVO-RS-UA, Avantes) as described in the work of Roibu et al To initiate the measurement, an external trigger connected to the spectrometer was used. A schematic representation of the experimental setup is provided in Figure .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…It was concluded that the photon flux per unit volume and the hydrodynamics did not depend on the gas content for a wide range of flow conditions, which showed the high flexibility of the AFR. In that work, an empirical formula was suggested for the optical path length [76].…”
Section: Photon Transportmentioning
confidence: 99%